2011
DOI: 10.26493/1855-3974.127.eb9
|View full text |Cite
|
Sign up to set email alerts
|

The symmetric genus spectrum of finite groups

Abstract: The symmetric genus of the finite group G, denoted by σ(G), is the smallest nonnegative integer g such that the group G acts faithfully on a closed orientable surface of genus g (not necessarily preserving orientation). This paper investigates the question of whether for every non-negative integer g, there exists some G with symmetric genus g. It is shown that that the spectrum (range of values) of σ includes every non-negative integer g ≡ 8 or 14 mod 18, and moreover, if a gap occurs at some g ≡ 8 or 14 modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A natural problem is to determine the positive integers that occur as the symmetric genus of a group (or a particular type of group), that is, to determine the symmetric genus spectrum for the particular type of group. Important results about the symmetric genus spectrum of all finite groups were obtained by Conder and Tucker [1]. They showed that the symmetric genus spectrum of finite groups contains well over 88 percent of all positive integers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A natural problem is to determine the positive integers that occur as the symmetric genus of a group (or a particular type of group), that is, to determine the symmetric genus spectrum for the particular type of group. Important results about the symmetric genus spectrum of all finite groups were obtained by Conder and Tucker [1]. They showed that the symmetric genus spectrum of finite groups contains well over 88 percent of all positive integers.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the symmetric genus spectrum of finite groups contains well over 88 percent of all positive integers. In particular, they showed that if g is any non-negative integer such that g is not congruent to 8 or 14 (mod 18), then g is in the spectrum [1,Theorem 1.2]. However, there are no known gaps in the spectrum, and evidence suggests that there are none.…”
Section: Introductionmentioning
confidence: 99%
“…The symmetric genus is the smallest non-negative integer g such that the group G acts faithfully on a closed orientable surface of genus g (not necessarily preserving orientation). For this parameter, the spectrum includes every non-negative integer g ≡ 8 or 14 (mod 18), and moreover, if a gap occurs at some g ≡ 8 or 14 (mod 18), then the prime-power factorization of g − 1 includes some factor p e ≡ 5 (mod 6), [11]. In the study of the spectrum of the symmetric crosscap number, the groups with symmetric crosscap number of the form 12k + 3 are very interesting.…”
Section: Preliminariesmentioning
confidence: 99%
“…The three automorphisms of order 2 of the maximal cyclic group will be called inversion, the quasi-dihedral action and the quasi-abelian action; these actions are given in (3), (4) and (5), respectively. Inversion is also used to construct a dicyclic group, but the element of the group that gives rise to the inner automorphism which is inversion has order 4.…”
Section: Preliminariesmentioning
confidence: 99%
“…Indeed, whether or not there is a group of symmetric genus n for each value of the integer n remains a challenging open question; see the recent, important article [4]. Here, we restrict our attention to 2-groups.…”
Section: Introductionmentioning
confidence: 99%